1991
DOI: 10.1093/oxfordjournals.annonc.a057906
|View full text |Cite
|
Sign up to set email alerts
|

BOP/VIP - A new platinum-intensive chemotherapy regimen for poor prognosis germ cell tumours

Abstract: Ninety-one patients with poor prognosis non-seminomatous germ cell tumours (NSGCT) were treated with an initial intensive chemotherapy schedule. Suitable patients fulfilled one or more of the following criteria: lymph node metastases greater than 10 cm diameter; liver, brain or bone metastases; serum HCG level greater than 50,000 IU/L; and extragonadal primary tumours. Treatment consisted of 3 cycles of bleomycin, vincristine and cisplatin (BOP) administered at 10 day intervals, followed by 3 cycles of etoposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Suggestive evidence to support this notion is provided by observations in poor risk germ cell tumours, where closely spaced cisplatin therapy has been investigated (Ozols et al, 1988;Horwich et al, 1989;Lewis et al, 1991). Early studies with weekly administration of cisplatin were hampered by the side effects which can nowadays be partly prevented (Corder et al, 1977;Randolph et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Suggestive evidence to support this notion is provided by observations in poor risk germ cell tumours, where closely spaced cisplatin therapy has been investigated (Ozols et al, 1988;Horwich et al, 1989;Lewis et al, 1991). Early studies with weekly administration of cisplatin were hampered by the side effects which can nowadays be partly prevented (Corder et al, 1977;Randolph et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…One patient developed a secondary leukaemia, a phenomenon that has been extensively described in germ-cell tumour survivors (Bokemeyer and Schmoll, 1995). Relatively high rates of toxicity-related death have previously been reported in patients treated with dose-dense regimens (Bower et al, 1997;Kaye et al, 1998;Lewis et al, 1991;Horwich et al, 1994Horwich et al, , 1997Harstrick et al, 1991;Germa Lluch et al, 1992. For example, 6.5% and 7% patients died of toxicity after they had received the BOP/VIP-B and the C-BOP-BEP regimens, respectively (Kaye et al, 1998;Horwitch et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Finally the Medical Research Council and the EORTC have reported the results of a phase III trial that compared a rapidly recycled intensive regimen (BOP/VIP-B) to the standard 4 BEP in 380 patients with poor-prognosis NSGCT (Kaye et al, 1998). Unfortunately, the BOP/VIP-B regimen, which was initially reported to be highly efficient in 91 patients treated in an uncontrolled study (Lewis et al, 1991) did not afford any survival benefit in this randomised study. Possible explanations for these negative results are a higher number of toxicity-related deaths (12 vs 4) and a higher proportion (10% vs 5%) of primary mediastinal NSGCT, notorious for their poor outcome (Fizazi et al, 1998), in the intensive arm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently the overall cure rate for this tumour is of the order of 90% (Loehrer et al, 1988), although for patients with the most advanced metastatic disease, the prospect of cure is somewhat lower, at approximately 40-70% (Lewis et al, 1991). The optimal management strategy for these patients with large volume metastatic disease has not yet been fully defined.…”
mentioning
confidence: 99%